Tempo e prestação de tutela jurisdicional executiva: um diagnóstico, no âmbito do Tribunal de Justiça de Pernambuco, do tempo de trâmite das principais etapas do processo de execução de título extrajudicial. - Tenório, Gabriela Luna Santana Gomes (2023)
Which endoprocedural factors are related to the variation in the chances of having a slower or faster civil enforcement? The discussion matters, considering that the lack of effectiveness of enforcement proceedings has a significant impact on the time of judicial lawsuits and compromises the image of the Judiciary. In regard to methodology, an exploratory quantitative empirical research was carried out. About the data, it was collected a statistically representative sample of some lawsuits, between 2015 and 2020, of the Pernambuco Justice Court. The data was submitted to logistic regression analysis. Furthermore, it was possible to verify that the point of view of the scholars about the research theme is not at all far removed from the reality. Finally, this research has contributed to confirming the main endoprocedural factors that influence the time it takes to carry out enforcement proceedings.